Developments and debates on latent variable modeling in diagnostic studies when there is no gold standard. Issue 2 (3rd July 2021) - Wang, Zheyu
Abstract : Latent variable modeling is often used in diagnostic studies where a gold standard reference test is not available. Its applications have become increasing popular with the fast discovery of novel biomarkers and the effort to improve healthcare for each individual. This paper attempt to provide a review on current developments and debates of these models with a focus in diagnostic studies and to discuss the value as well as cautionary considerations in the applications of these models.